(untitled) (Journal on studies and research of academic knowledge, 2016)
Yerba Mate is a native tree species of flora and under such conditions was part of the forest’s ecosystem. The environmental balance has been broken with the advancement of agroforestry practices. There is a greater amount of food to some species of complex phytopathogenic fungi, which greatly increase their number, becoming diseases of yerba mate with the increase of the plantation areas. Up to today, we have no proven effective solution for the problem generated by fungicide. This situation has been satisfactorily resolved with an extensive study of complex phytopathogenic fungi of the yerba plantation and the application of chemical fungicide. It can be achieved a 60% of effectiveness in the control of defoliation with the right treatment.